Competition in Indian life insurance industry: post liberalisation evidence. (2016) - Parida, Tapas Kumar; Acharya, Debashis
This paper makes an attempt to assess the state of competition in the Indian life insurance industry for the period 2000-01 to 2014-15 highlighting the nature of competition after the economic reforms in the economy. The study is based on secondary data of the insurance companies for the period 2000-01 to 2014-15. A set of concentration measures such as the k-concentration ratio (CRk), Herfindahl-Hirschman index (HHI), the Hall-Tideman index (HTI), Horvath index (HOV), Entropy index (ENT), Ginevicius index, and GRS index is estimated to assess the state of competition. Accuracy of these indices is also tested along with use of concentration curves and indices. Among all the concentration measures, HHI, HTI and GIN indices depict the low market concentration of life insurance companies, compared to other indices. The index value indicates that though the concentration in the market has declined but still it remains at a relatively higher level.